Mas mato la cena, que sano Avicena. Proverbialisation of historical and literary figures in Spanish and Polish - Szymanski, Jakub (Romanica Olomucensia, 2024)
This article contributes to the study of contrastive paremiology in Spanish and Polish. It focuses on the proverbialisation of historical and literary figures in the collections of proverbs of these two languages. The study aims to cast light upon the incorporation of this type of character in paremias in relation to the culture of each linguistic community. The corpus of decontextualised paremias of a popular character consists of 305 paremias extracted manually from one Polish and four Spanish dictionaries of proverbs and was subjected to quantitative and qualitative analysis. The working methodology was based on the procedures of the members and collaborators of the PAREFRAS research group, as well as on the work of paremiologists using ethnolinguistic methods. A classification of the historical-literary figures present in the proverbs was also outlined. The analysis reveals that there are significantly more historical and literary figures in Polish, and that more historical than literary characters are included in both languages. Moreover, the two collections of proverbs share very few common figures. The origin of the characters is mainly internal, most of them are from the privileged classes, and very few female figures are recorded. The study confirms that there is a strong relationship between the proverbs of each linguistic community and its culture, as well as concluding that as a result of the incorporation of mostly figures from the upper classes, these characters endure more in the collective memory, while the memory of the common people disappears.
Keywords: paremiology; proverb; historical and literary characters; proverbialisation; ethnolinguistics